Search for squarks and gluinos in events with hadronically decaying tau leptons, jets and missing transverse momentum in proton-proton collisions at [Formula: see text] TeV recorded with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2016)
A search for supersymmetry in events with large missing transverse momentum, jets, and at least one hadronically decaying tau lepton has been performed using 3.2 fb[Formula: see text] of proton-proton collision data at [Formula: see text] recorded by the ATLAS detector at the Large Hadron Collider in 2015. Two exclusive final states are considered, with either exactly one or at least two tau leptons. No excess over the Standard Model prediction is observed in the data. Results are interpreted in the context of gauge-mediated supersymmetry breaking and a simplified model of gluino pair production with tau-rich cascade decays, substantially improving on previous limits. In the GMSB model considered, supersymmetry-breaking scale ([Formula: see text]) values below [Formula: see text] are excluded at the 95% confidence level, corresponding to gluino masses below [Formula: see text]. For large values of [Formula: see text], values of [Formula: see text] up to [Formula: see text] and gluino masses up to [Formula: see text] are excluded. In the simplified model, gluino masses are excluded up to [Formula: see text] for neutralino masses around [Formula: see text]. Neutralino masses below [Formula: see text] are excluded for all gluino masses between 800 and [Formula: see text], while the strongest exclusion of [Formula: see text] is achieved for gluino masses around [Formula: see text].